Continuous and gradual photo-activation methods: influence on degree of conversion and crosslink density of composite resins - Costa, S. X. S. [UNESP]; Galvao, M. R. [UNESP]; Jacomassi, D. P.; Bernardi, M. I. B.; Hernandes, A. C.; Rastelli, Alessandra Nara de Souza [UNESP]; Andrade, M. F. [UNESP] (Springer, 2011)
Thermal properties and degree of conversion (DC%) of two composite resins (microhybrid and nanocomposite) and two photo-activation methods (continuous and gradual) displayed by the light-emitting diode (LED) light-curing units (LCUs) were investigated in this study. Differential scanning calorimetry (DSC) thermal analysis technique was used to investigate the glass transition temperature (T-g) and degradation temperature. The DC% was determined by Fourier transform infrared spectroscopy (FT-IR). The results showed that the microhybrid composite resin presented the highest T-g and degradation temperature values, i.e., the best thermal stability. Gradual photo-activation methods showed higher or similar T-g and degradation temperature values when compared to continuous method. The Elipar Freelight 2 (TM) LCU showed the lowest T-g values. With respect to the DC%, the photo-activation method did not influence the final conversion of composite resins. However, Elipar Freelight 2 (TM) LCU and microhybrid resin showed the lowest DC% values. Thus, the presented results suggest that gradual method photo-activation with LED LCUs provides adequate degree of conversion without promoting changes in the polymer chain of composite resins. However, the thermal properties and final conversion of composite resins can be influenced by the kind of composite resin and LCU.
Keywords: Fourier transform infrared spectroscopy; Differential scanning calorimetry; LED; Dental curing lights; Composite resins